O problema do mal livro VII das confissões de Santo Agostinho - Silva, Fagner Veloso da Silva (2017)
In this dissertation we focus on the investigation about the bad based on the book VII of the Saint Augustine’s confessions, how to bad became a problem to Saint Augustine and how he searched a resolution for that was distressing for his life. The tipology was to discursivs, bibliographical research,from the lifting of antimanichaeism works of Saint Augustine.The bishop of Hippo researched the several philosophical and religious streams, the Neoplatonism and Manichaeism. However, the answers that these streams gave to the bad problematic weren’t enough to the unquiet mind of the Hipponense.This way, the main problem that was investigated in this dissertation is the conducting wire of the Augustine’s thoughts about his difficult in to accept the bad nature and its source. Because of this, the base of our investigation is the referred book VII of Augustine’s confessions. We listed what influenced the Hiponense to involve wit this subject, that is, what meaning of his life instigated him to involve and to think about the problem of the bad and, consequently, to try give an answer that exempts God to be the source of the bad. What elements made him to think and establish the Jewish- Christian like the only ontological principle that have countered the Manichaean duality. And, consequently, what’s the function that wish plays on the human actions.Our research was structured in three moments:in the first, we make a contextualization of the social,historical, and philosophical ambit of the work Saint Augustine’s confessions; in the second moment, we present the augustine’s mishap looking for the answer to the problem of bad;and, finally, we discuss specifically about theproblem of the bad in Augustine.